1990
DOI: 10.3109/07853899009147253
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Evaluation of Epithelial Cell Function by CA 125 and Stromal Cell Activity by Aminoterminal Propeptide of Type III Procollagen (PIIINP) in Ovarian Carcinoma

Abstract: Serum concentrations of CA 125 and the aminoterminal propeptide of type III procollagen (PIIINP) were measured in 50 patients with clinical stage I or II (N = 16) and stage III or IV (N = 34) ovarian carcinoma before and during cytotoxic chemotherapy. Initially pathological concentrations of CA 125 were found in 92% of all patients and 100% of those in clinical stages II, III and IV. The concentration of PIIINP was at pathological levels in 71% of patients. Serum concentrations of CA 125 (P = 0.04) and PIIINP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In patients with benign cystadenomas of the ovary, the PIIINP concentrations do not differ from those in age-matched control persons (13). In a prospective study we found a negative correlation between the initial PIIINP concentration and survival time (p = 0.01) in patients who died during the follow-up period of 1-19 months (15) . No such relationship was found between CA 125 and survival time .…”
Section: Biochemical Basis For the Piiinp Measurementmentioning
confidence: 64%
See 2 more Smart Citations
“…In patients with benign cystadenomas of the ovary, the PIIINP concentrations do not differ from those in age-matched control persons (13). In a prospective study we found a negative correlation between the initial PIIINP concentration and survival time (p = 0.01) in patients who died during the follow-up period of 1-19 months (15) . No such relationship was found between CA 125 and survival time .…”
Section: Biochemical Basis For the Piiinp Measurementmentioning
confidence: 64%
“…We have studied the concentration of PIIINP in serum in several series of patients with ovarian carcinom a. both retrospectively and prospectively (13)(14)(15). Elevated values are quite common , occurring in about 80% of the patients with advanced disease before chemotherapy (Fig.…”
Section: Biochemical Basis For the Piiinp Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them contracted recurrent cancer 8 months after operation. Six patients responded to cytotoxic chemotherapy by stabilization of the disease, which was transient in two cases (progression at 7 and 8 months) and which still continues in four patients at the end of the follow-up (16,18,19, and 40 months). In 12 patients, the malignancy progressed continuously.…”
Section: Methodsmentioning
confidence: 96%